Metabolic Inflexibility with Obesity and the Effects of Fenofibrate on Skeletal Muscle Fatty Acid Oxidation - Boyle, Kristen E.; Friedman, Jacob E.; Janssen, Rachel C.; Underkofler, Chantal; Houmard, Joseph A.; Rasouli, Neda (Hormone and Metabolic Research, 2017)
This study was designed to investigate mechanisms of lipid metabolic inflexibility in human obesity and the ability of fenofibrate (FENO) to increase skeletal muscle fatty acid oxidation (FAO) in primary human skeletal muscle cell cultures (HSkMC) exhibiting metabolic inflexibility. HSkMC from 10 lean and 10 obese, insulin resistant subjects were treated with excess fatty acid for 24 h (24hFA) to gauge lipid-related metabolic flexibility. Metabolically inflexible HSkMC from obese individuals were then treated with 24hFA in combination with FENO to determine effectiveness for increasing FAO. Mitochondrial enzyme activity and FAO were measured in skeletal muscle from subjects with prediabetes (n=11) before and after 10 weeks of fenofibrate in vivo. 24hFA increased FAO to a greater extent in HSkMC from lean versus obese subjects (+49% vs. +9%, for lean vs. obese, respectively; p<0.05) indicating metabolic inflexibility with obesity. Metabolic inflexibility was not observed for measures of cellular respiration in permeabilized cells using carbohydrate substrate. Fenofibrate co-incubation with 24hFA, increased FAO in a subset of HSkMC from metabolically inflexible, obese subjects (p<0.05), which was eliminated by PPARα antagonist. In vivo, fenofibrate treatment increased skeletal muscle FAO in a subset of subjects with prediabetes but did not affect gene transcription or mitochondrial enzyme activity. Lipid metabolic inflexibility observed in HSkMC from obese subjects is not due to differences in electron transport flux, but rather upstream decrements in lipid metabolism. Fenofibrate increases the capacity for FAO in human skeletal muscle cells, though its role in skeletal muscle metabolism in vivo remains unclear.
Keywords: mitochondria; fat oxidation; insulin resistance